Constituents of Fevillea cordifolia: New Norcucurbitacin and Cucurbitacin Glycosides - Achenbach, Hans (1993)
The seeds of Fevillea cordifolta have yielded 11 new fevicordin-type 29- norcucurbitacins 3-13, and two new cucurbitacin glycosides 14 and 15, which were isolated along with previous reported fevicordin A [2] and its glucoside [1]. Structure determinations are based on spectroscopic studies and on chemical interconversions.